Rapid Growth of Hotels in Yogyakarta and Its Relation to the City's Water Supply - Manifesty, Odilia Renaningtyas (E-Journal of Tourism; Volume 6 Number 1 (March 2019)DO - 10.24922/eot.v6i1.41878, 2019)
As tourist destination, Yogyakarta offers a complete tourism package from man-made environment such as Ullen Sentalu Museum and the ancient temples to natural environment such as Mount Merapi. Roughly five million tourists, both locals and foreigners, were visiting the city in 2017. Furthermore, eighty percent of the tourists are reported staying at hotels and any other form of accommodation. The high number in accommodation demand makes hospitality business to flourish and more hotels to be built. However, the stated development might violate the environmental carrying capacity. The concern rises after the city’s residents started to link the growth of hotels development with water shortage in several parts of the city. Two sets of urban layer related to clean water supply is presented and ,with the support of numerical data about the growth of tourist accommodation, is analyzed to give scientific base to the issue and as preliminary study on formulating the solution to the issue.